Minorities New Studies and Perspectives - Hermann, John R. (IntechOpen, 2023)
Minorities - New Studies and Perspectives offers important and innovative research on the oppression of minorities by the majority. The treatment of minorities is explored from multiple dimensions in this academic work. Firstly, the book investigates the issue of lack of equal opportunity, including discrimination based on race, gender, sexuality, religion, disability, ethnicity, and other factors. Secondly, the authors analyze institutional and structural barriers that prevent equal opportunity in various settings, such as healthcare, the criminal justice system, education, voting, government and corporate policies, and immigration and migration. Thirdly, the book delves into the concept of racial threats and critical race theory, including topics such as microaggressions, majority oppression, minority identity, and intersectionality. Finally, the authors present strategies for overcoming unfair treatment of minorities, such as affirmative action, civil rights legislation, court decisions, and corporate policies. Overall, this edited volume provides a diverse and contemporary examination of minority issues.